XRCC1 deficient triple negative breast cancers are sensitive to ATR, ATM and Wee1 inhibitor either alone or in combination with olaparib. (December 2020) - Ali, Reem; Alblihy, Adel; Toss, Michael S.; Algethami, Mashael; Al Sunni, Rabab; Green, Andrew R.; Rakha, Emad A.; Madhusudan, Srinivasan
Background: PARP inhibitor (PARPi) monotherapy is a new strategy in BRCA germ-line deficient triple negative breast cancer (TNBC). However, not all patients respond, and the development of resistance limits the use of PARPi monotherapy. Therefore, the development of alternative synthetic lethality strategy, including in sporadic TNBC, is a priority. XRCC1, a key player in base excision repair, single strand break repair, nucleotide excision repair and alternative non-homologous end joining, interacts with PARP1 and coordinates DNA repair. ATR, ATM and Wee1 have essential roles in DNA repair and cell cycle regulation. Methods: Highly selective inhibitors of ATR (AZD6738), ATM (AZ31) and Wee1 (AZD1775) either alone or in combination with olaparib were tested for synthetic lethality in XRCC1 deficient TNBC or HeLa cells. Clinicopathological significance of ATR, ATM or Wee1 co-expression in XRCC1 proficient or deficient tumours was evaluated in a large cohort of 1650 human breast cancers. Results: ATR (AZD6738), ATM (AZ31) or Wee1 (AZD1775) monotherapy was selectively toxic in XRCC1 deficient cells. Selective synergistic toxicity was evident when olaparib was combined with AZD6738, AZ31 or AZD1775. The most potent synergistic interaction was evident with the AZD6738 and olaparib combination therapy. In clinical cohorts, ATR, ATM or Wee1 overexpression in XRCC1 deficient breast cancer was associated with poor outcomes. Conclusion: XRCC1 stratified DNA repair targeted combinatorial approach is feasible and warrants further clinical evaluation in breast cancer.